Chalcogenide Thin Films Prepared using Chemical Bath Deposition Method: Review - Ho, Soon Min (Maxwell Scientific Publication Corp, 2015)
The aim of this study is to discuss the synthesis of thin films using chemical bath deposition method. In recent years, studies of thin films of different groups have attracted great attention due to their applications are possible in many areas of modern technology. Researchers have deposited binary, ternary and quaternary thin films from aqueous solutions using chemical bath deposition method. Here, the growth of metal sulfide, selenide and telluride thin films has been reported. The influence of deposition parameters on the physical properties of films was investigated. The research findings indicate that an increase in deposition time allows more materials to be deposited onto the substrate. Morphological studies of films show that the films thicknesses were increased as the bath temperature was increased.